2008
DOI: 10.1136/bmj.a2001
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of micronutrient supplementation during pregnancy on birth weight, duration of gestation, and perinatal mortality in rural western China: double blind cluster randomised controlled trial

Abstract: Objective To examine the impact of antenatal supplementation with multiple micronutrients or iron and folic acid compared with folic acid alone on birth weight, duration of gestation, and maternal haemoglobin concentration in the third trimester. Design Cluster randomised double blind controlled trial. Setting Two rural counties in north west China. Participants 5828 pregnant women and 4697 live births. Interventions Villages were randomised for all pregnant women to take either daily folic acid (control), iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
286
5
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(318 citation statements)
references
References 25 publications
10
286
5
11
Order By: Relevance
“…The trial in Tanzania that used much higher doses of vitamin E and B, but removed vitamin A and zinc, reported a response similar to what we found in Indonesia (Fawzi et al, 2007). In China, comparing the UN International Multiple Micronutrient Preparation formulation with the standard dose of IFA, which is twice as much as in our study resulted in a mean birthweight increase similar to our findings, but there was little difference found in the LBW response (Zeng et al, 2008). Interestingly, a study in Burkina Faso (Roberfroid et al, 2008) and in Indonesia (Sunawang et al, 2009) that studied similar comparison reported a slightly greater increase in birthweight and a similar reduction in LBW compared with our results.…”
Section: Discussionsupporting
confidence: 88%
“…The trial in Tanzania that used much higher doses of vitamin E and B, but removed vitamin A and zinc, reported a response similar to what we found in Indonesia (Fawzi et al, 2007). In China, comparing the UN International Multiple Micronutrient Preparation formulation with the standard dose of IFA, which is twice as much as in our study resulted in a mean birthweight increase similar to our findings, but there was little difference found in the LBW response (Zeng et al, 2008). Interestingly, a study in Burkina Faso (Roberfroid et al, 2008) and in Indonesia (Sunawang et al, 2009) that studied similar comparison reported a slightly greater increase in birthweight and a similar reduction in LBW compared with our results.…”
Section: Discussionsupporting
confidence: 88%
“…3 Combined with the results of the Chinese trial mentioned above, 5 our findings indicate that antenatal care should include the promotion and supply of iron and folic acid supplementation for pregnant women as a key intervention.…”
Section: Discussionmentioning
confidence: 53%
“…In contrast, a recent large trial in China reported a 54% greater reduction in early neonatal mortality among neonates whose mothers received iron and folic acid supplements compared to those whose mothers received folic acid alone. 5 The lower mortality was associated with a significant reduction in the risk of early preterm delivery and with fewer deaths from birth asphyxia. These findings are consistent with trials in non-anaemic women in the United States of America (USA), which have demonstrated that the incidence of preterm birth is significantly lower in mothers who receive iron supplements.…”
Section: Introductionmentioning
confidence: 97%
“…At the moment, conflicting evidence from studies on multiple micronutrients during pregnancy on infant mortality make it hard for public health policy makers to draw conclusions. For example, in Nepal, addition of zinc to iron þ folic acid supplements nullified the beneficial effect of iron þ folic acid on birth weight (Christian et al, 2003), whereas in China, multiple micronutrient supplementation during pregnancy improved birth weight, but had no effect on early neonatal mortality (Zeng et al, 2008). Long-term follow-up of newborns is needed to understand long-lasting effects of maternal and neonatal nutritional status and micronutrient supplementation on immune function and health.…”
mentioning
confidence: 99%